(untitled) (Research, Society and Development, 2022)
Objective: There is limited understanding of peculiarities in the health care of sexual and gender minorities (SGM). This study aimed at needs such as clinical and main barriers of the population and homosexuals in the scenario of transformation. Methodology: An integrative literature review was carried out, using as online databases: MEDLINE, VHL and LILACS of the last 5 years, using the guiding question: "What are the current ones for health care in gynecology for transgender and gay men, to health protection and disease prevention?” Results: At the end of the searches, 13 publications met the eligibility criteria and were selected to compose the study. They were reviewed as specific for promoting the health of transgender men and homosexual women, regarding gynecological consultation, cancer and STI prevention and reproductive planning. Knowledge of health needs allows the development of a welcoming and inclusive practice for SGMs. Education education and training among health providers and professionals can improve the sense of understanding how health screening and health fundraising can increase disparities. Conclusion: Health professionals should become familiar with the unique health care needs of people who identify as transgender men and gay women. Social determinants can influence gynecological care for SGMs, which can generate disparities among different marginalized groups.